2011
DOI: 10.1002/jhm.711
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific reference values for cerebrospinal fluid protein concentration in neonates and young infants

Abstract: BACKGROUND: Cerebrospinal fluid (CSF) protein values decline over the first few months of life as the infant's blood‐CSF barrier matures. However, published studies differ in the reported rate, timing, and magnitude of this decline. OBJECTIVE: To quantify the age‐related changes in CSF protein concentration and to determine accurate, age‐specific reference values for neonates and young infants. DESIGN, SETTING AND PATIENTS: This cross‐sectional study included infants age 56 days or younger who had a lumbar pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…In studies that have excluded infants with "traumatic taps" (or nonbacterial illnesses), the mean number of white blood cells in uninfected preterm or term infants was consistently <10 cells/mm 3 . [44][45][46][47][48][49][50] Cell counts 2 standard deviations from the mean were generally less than 20 cells/mm 3 . 46 In a study by Garges et al, the median number of white blood cells in infants who were born at greater than 34 weeks' gestation and had bacterial meningitis was 477/mm 3 .…”
Section: Lumbar Puncturementioning
confidence: 91%
See 1 more Smart Citation
“…In studies that have excluded infants with "traumatic taps" (or nonbacterial illnesses), the mean number of white blood cells in uninfected preterm or term infants was consistently <10 cells/mm 3 . [44][45][46][47][48][49][50] Cell counts 2 standard deviations from the mean were generally less than 20 cells/mm 3 . 46 In a study by Garges et al, the median number of white blood cells in infants who were born at greater than 34 weeks' gestation and had bacterial meningitis was 477/mm 3 .…”
Section: Lumbar Puncturementioning
confidence: 91%
“…55 Protein concentrations in uninfected, term newborn infants are <100 mg/ dL. [44][45][46][47][48][49][50] Preterm infants have CSF protein concentrations that vary inversely with gestational age. In the normoglycemic newborn infant, glucose concentrations in CSF are similar to those in older infants and children (70%-80% of a simultaneously obtained blood specimen).…”
Section: Lumbar Puncturementioning
confidence: 99%
“…55 The CSF protein concentration in the term uninfected infant is usually less than 100 mg/dL; the CSF protein concentration of the uninfected preterm infant is higher than the term infant and is correlated with prematurity. 56 The CSF glucose concentration in the term infant is usually between 70% and 80% of a simultaneously measured serum glucose; a low CSF glucose has the greatest specificity for bacterial meningitis. 37,57 Bacterial meningitis may occur in infants with normal CSF parameters who concomitantly have a high concentration of bacterial organism.…”
Section: Csf Cell Count and Chemistriesmentioning
confidence: 99%
“…4 The interpretation of CSF protein levels is further complicated in the youngest infants due to both the changing composition of the CSF as well as the higher rates of traumatic LPs. 5 Therefore, studies establishing a correction factor, adjusting observed CSF protein levels for the presence of CSF RBCs, that included predominantly older children may not be generalizable to neonates and young infants. 6 We sought to determine the relationship between CSF RBC count and CSF protein in infants 56 days of age who underwent LP in the emergency department (ED).…”
Section: Discussionmentioning
confidence: 99%